MOTIVASI BELAJAR SISWA KELAS KHUSUS DAN KELAS REGULER DI MTsN 4 BANDA ACEH - Wanty Khaira; Mita Hasanah (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2022)
Learning motivation is a psychological condition that encourages someone to do something that will cause changes in human activity. A person's learning motivation is influenced by two factors, namely intrinsic factors which include physiological (physical condition) and psychological (attitudes, talents, interests, intelligence, and cognitive abilities). While the second factor is extrinsic factors which include the environment (natural and social), parental attention, curriculum, teachers, learning facilities, teaching methods, and administration. This research was conducted at MTsN 4 Banda Aceh, this study aims to determine the differences in learning motivation between students in special and regular classes. This study is a comparative study, the population in this study were all students of MTsN 4 Banda Aceh as many as 565 students, the sample in this study was 168 students who were determined by simple random sampling technique consisting of 84 special class students and 84 regular class students. The data collection technique was carried out using a Likert scale, data analysis was carried out by using the t test (Independent Sample T-Test). The results showed that there was a difference in learning motivation between special class students and regular class students as indicated by the tcount coefficient of 1,983 which was greater than ttable of 1,974 (1,983>1,974) and the significance value of 0.000 was smaller than 0.05 (0.000<0, 05). So the result is that Ho is rejected and Ha is accepted, meaning that there is a difference in learning motivation between students in the special class and the regular class.